ESTABLISHMENT OF BRAND ENGAGEMENT TO CUSTOMERS OF BEAUTIFUL HOMES IN THE CITY OF BANGKINANG THROUGH BRAND POSTS ON SOCIAL MEDIA - Rosdianti Rosdianti; Samsurijal Hasan; Litra Diantara (STIE Bangkinang Publishing, 2022)
One of the marketing activities for beauty services is promotion. The promotional activities carried out by the beauty service house are expected to be able to market according to the principles of marketing beauty services that are in accordance with facts, are honest, informative and educational. Promotion, which is one of the marketing activities for beauty services, is one form of advertising, which can be done through conventional media and digital media. To expand its reach in marketing beauty services, digital media can be used, one of which is through social media. Rumah Cantik Nitri in Bangkinang City has limited use of social media for promotional activities. Meanwhile, the target market is a community that is familiar with social media. Furthermore, the official Fecebook and Instagram of Rumah Cantik Nitri have not been managed professionally so that they have not made a significant contribution to the marketing performance of these services. The objects in this study are brand posts, comments, replies, the number of likes and shares that occur on social media accounts Facebook and Instagram owned by Rumah Cantik Nitiri in Bangkinang City. Rumah Cantik Nitri, in terms of utilizing social media channels, prioritizes Instagram and Facebook as information media and interacts with consumers and does more neutral brand posts and uses them as online customer care media with a very fast response. At Rumah Cantik Nitri, the social media that is most capable of generating brand engagement is Instagram social media. This can be seen from consumer responses in the form of product reviews and user generated content with the highest number compared to other social media because the interactions that occur are more active than other social media. Brand engagement created at Rumah Cantik Nitri, brand posts that are posted are still at the stage of attracting attention (awareness) by creating an informational brand post which aims to introduce beauty services to attract more users by following their social media.